Surgical treatment of chronic thromboembolic pulmonary hypertension in combination with a left anterior descending artery myocardial bridge: A case report - Zugurov, Ilkhom K.; Osadchii, Aleksei M.; Simakova, Maria A.; Moiseeva, Olga M.; Gordeev, Mikhail L. (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary thromboendarterectomy is a potentially curative option for most of the patients with chronic thromboembolic pulmonary hypertension (CTEPH). However, there is a special group of CTEPH patients who require simultaneous cardiac procedures. We report a rare case of successful surgical treatment of CTEPH patient with left anterior descending artery myocardial bridge. Despite the complexity of performing pulmonary thromboendarterectomy (PTE), the issue concerning the method of revascularization of the artery in case of left anterior descending artery myocardial bridge is controversial. PTE and supracoronary myotomy were performed. In our case, the optimal method of surgery for the left anterior descending artery myocardial bridge was chosen intraoperatively based on the depth and length of the myocardial bridge. The patient significantly functional improved after surgery and hemodynamic normalization was confirmed at follow-up assessment. This case demonstrates rare but potentially dangerous pathologies that can be treated with minimal adverse effect.